Seed Biology of Witchgrass (Panicum capillare L.) Ensures Its Success Under Different Environmental Conditions - Wu, Hanwen; Asaduzzaman, Md; Shephard, Adam; Ma, Xiaoyan (Frontiers in Agronomy, 2021)
Witchgrass (Panicum capillare L.) is a summer growing grass weed species and is increasing its prevalence in southern Australia. A better understanding of the seed biology is needed to effectively manage this weed. A series of field and laboratory studies were conducted to determine seed germination factors, field emergence patterns and soil seedbank longevity. Witchgrass germination was stimulated by light and it germinated better at temperature over 20 °C, with 93-100% germination at the two constant temperatures of 20 and 30 °C, and the two alternating day /night temperatures of 30/25 and 35/25 °C. It is highly tolerant to moisture stress at germination, with 2-7% germination even at -0.48 Mpa. Witchgrass seed lost 47-68% viability after 12 months of burial in the soil, however the seed persisted for more than 4 years if buried at 10 cm in the soil. Witchgrass emergence in southern New South Wales (NSW) commenced in mid spring (early October), with peak emergence of 63-83% in November and then significantly reduced to 16-37% emergence in December. Little emergence (< 1%) occurred in the summer months from January to February. These results provide useful information for designing effective management strategies and the optimum timing of control. Climate change could favour the phenological development and the further spread of this weed, which present new challenges for its effective management. Further study is needed to investigate the impact of climate change on the biology, spread and management of witchgrass.